INTERAKSI SOSIAL DALAM KELOMPOK TANI SEHATI DI KELURAHAN KAKASKASEN DUA KOTA TOMOHON (SOSIAL INTERACTION IN FARMER SEHATI GROUPS IN THE KAKASKASEN DUA SUB DISTRICT OF TOMOHON CITIE) - Christy Mikhael Ester Lingga; Melsje Yellie Memah; Noortje Marselianie Benu (Sam Ratulangi University, 2021)
This study aims to describe the level of social interaction in the Sehati farmer group in Kakaskasen Dua Village, Tomohon City which consists of cooperation, accommodation, and assimilation. This research was conducted from May to March January. The data used in this study are primary data and secondary data. Primary data were obtained through direct interviews with 10 respondents consisting of KSB and all members of the Sehati Farmer Group using a questionnaire, while secondary data were obtained from BP3K, literature, and previous research related to this study. Methods of data collection were carried out using a survey, and measured using a Likert scale. The results showed that, the level of social interaction in the Sehati farmer group in Kelurahan Kakaskasen Dua Tomohon City from the accommodation cooperation variable, the assimilation was 84.72%. Generally classified as Very Good. In particular, the level of interaction in the Sehati farmer group for the very good category, namely the accommodation variable was 85.33% and the assimilation variable was 89.83%. For the good category, namely the cooperation variable, amounting to 77.5%. The results showed that the social interaction of the Sehati farmer groups was very good except for the good cooperation. The results of the Likert analysis show that social interaction in the Sehati farmer group in Kakaskasen Dua Subdistrict, Tomohon City reaches 84.72% which means that it is in the very good category.